Regulatory of the Stock Market in Indonesia - Putri, Dinda Permata; Fahira, Dania Putri; Wardhany, Nurhastuty Kesumo (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The main purpose of this research is to deepen the exposure and analysis of the impact of changes in the stock market. Using a robust approach to statistical and econometric analysis, this study aims to identify patterns, trends and relationships between relevant variables in this context. The capital market is a very dynamic, interesting, constantly changing branch of the economy, which is one of the elements that will become a reference for the development of the country and the economy, where advanced industrial countries and new branches of the economy are characterized. by the fact that the capital market has grown and developed well. These characteristics arise from the need for an independent regulator that is ready to face the dynamics of change. Based on the Capital Markets Law No. 8 of 1995, BAPEPAM Capital Markets carries out daily guidance, regulation and supervision with the aim of carrying out an organized, fair and efficient operation of the capital market and protecting the interests of investors and the public. After the establishment of the Financial Services Authority with the adoption of the Financial Services Authority Act No. 21 of 2011, this authority became an independent body, replacing the supervisory function performed by BAPEPAM.